2022
DOI: 10.1038/s43856-022-00183-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modeling of vaccine deserts as barriers to controlling SARS-CoV-2

Abstract: Background COVID-19 vaccine distribution is at risk of further propagating the inequities of COVID-19, which in the United States (US) has disproportionately impacted the elderly, people of color, and the medically vulnerable. We sought to measure if the disparities seen in the geographic distribution of other COVID-19 healthcare resources were also present during the initial rollout of the COVID-19 vaccine. Methods Using a comprehensive COVID-19 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…The results contradict earlier randomized and non-randomized studies of the effectiveness of mask-wearing on the risk of infection [4,9,[19][20][21][22][23][24]. Most of these studies reported that wearing a face mask reduced the risk of COVID-19 infection.…”
Section: Discussioncontrasting
confidence: 78%
“…The results contradict earlier randomized and non-randomized studies of the effectiveness of mask-wearing on the risk of infection [4,9,[19][20][21][22][23][24]. Most of these studies reported that wearing a face mask reduced the risk of COVID-19 infection.…”
Section: Discussioncontrasting
confidence: 78%
“…Decreased access to vaccination has been observed in minoritized, lower-income, or rural communities, as vaccine administration locations were less likely to exist in these areas in the early vaccine rollout process. [44] , [45] These access barriers are related to socioeconomic conditions, but are distinct influences on vaccine uptake and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…California’s incidence of SARS-CoV-2 test positivity among workers by occupation and industry is undetermined, and signs and symptoms for worker populations have not yet been documented. Furthermore, while rural communities have experienced high COVID-19 mortality rates [ 16 ], faced barriers to tele-healthcare [ 17 ], and have less access to COVID-19 vaccines compared to urban counterparts [ 18 ], rural communities have largely been excluded from COVID-19 research, and little is known about their experience with occupational COVID-19 [ 19 ]. In order to guide workplace COVID-19 policies and recommendations, it is critical to understand which workers are exposed at work, how they may be exposed, and their health outcomes.…”
Section: Introductionmentioning
confidence: 99%